2016
DOI: 10.1111/gcb.13239
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for climate‐driven synchrony of marine and terrestrial ecosystems in northwest Australia

Abstract: The effects of climate change are difficult to predict for many marine species because little is known of their response to climate variations in the past. However, long-term chronologies of growth, a variable that integrates multiple physical and biological factors, are now available for several marine taxa. These allow us to search for climate-driven synchrony in growth across multiple taxa and ecosystems, identifying the key processes driving biological responses at very large spatial scales. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Drought conditions in this area are also linked to regional oceanographic indices (McCabe‐Glynn et al, ), so this long ecological cascade ultimately begins with ocean‐atmosphere interactions and ends up looping back onto the marine food web via murrelets. Similar synchronous effects between marine and terrestrial ecosystems have been increasingly recognized through the effects of rainfall (Black et al, ; Ong et al, ; Thomsen et al, ), but our study is unique for the California Current system in that long‐term data revealed a stronger connection between terrestrial productivity and the reproductive dynamics of a marine predator. In 2013, much of California was in an exceptional drought of a magnitude that had not been experienced for perhaps over ~1,200 years (Griffin & Anchukaitis, ; Diffenbaugh, Swain, & Touma, ).…”
Section: Discussionsupporting
confidence: 59%
“…Drought conditions in this area are also linked to regional oceanographic indices (McCabe‐Glynn et al, ), so this long ecological cascade ultimately begins with ocean‐atmosphere interactions and ends up looping back onto the marine food web via murrelets. Similar synchronous effects between marine and terrestrial ecosystems have been increasingly recognized through the effects of rainfall (Black et al, ; Ong et al, ; Thomsen et al, ), but our study is unique for the California Current system in that long‐term data revealed a stronger connection between terrestrial productivity and the reproductive dynamics of a marine predator. In 2013, much of California was in an exceptional drought of a magnitude that had not been experienced for perhaps over ~1,200 years (Griffin & Anchukaitis, ; Diffenbaugh, Swain, & Touma, ).…”
Section: Discussionsupporting
confidence: 59%
“…The correlation between ENSO and the LC strength affects species biology and ecology within WA waters. For example, La Niña events have positive impacts on growth rates of fish (Nguyen et al., ; Ong et al., ) and corals (Ong et al., ) and altered the distribution patterns of aggregating whale sharks ( Rhincodon typus ; Anderson et al., ; Wilson, Taylor, & Pearce, ). During the strong La Niña event in summer 2011, there was an extreme warming of SST with anomalies of 2–4 ° C persisting for several months (Pearce & Feng, ), during which ecosystems and marine species were affected (Feng, McPhaden, Xie, & Hafner, ; Smale & Wernberg, ; Wernberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by combining the environmental history and the otolith distance information, changes in fish reproductive phenology over time can be examined by a one-time sampling of juveniles and adults within different age classes based on the aforementioned assumptions. Past fish otolith studies using dendrochronological technologies have focused on understanding the changes in growth width chronologies in response to environmental change (Black et al, 2016;Izzo et al, 2016;Morrongiello et al, 2012;Ong et al, 2016), but no one has used these methods to help quantifying changes in fish reproductive phenology. Recently, the application of dendrochronology (tree-ring) technologies (crossdating) to fish otoliths has successfully addressed this challenge (Black et al, 2016;Morrongiello, Thresher, & Smith, 2012), thus providing the opportunity to investigate changes in fish reproductive phenology from otoliths.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of dendrochronology (tree-ring) technologies (crossdating) to fish otoliths has successfully addressed this challenge (Black et al, 2016;Morrongiello, Thresher, & Smith, 2012), thus providing the opportunity to investigate changes in fish reproductive phenology from otoliths. Past fish otolith studies using dendrochronological technologies have focused on understanding the changes in growth width chronologies in response to environmental change (Black et al, 2016;Izzo et al, 2016;Morrongiello et al, 2012;Ong et al, 2016), but no one has used these methods to help quantifying changes in fish reproductive phenology.…”
Section: Introductionmentioning
confidence: 99%